KRABBY KRONICLE – A COMEDIC EPISODE OF SPONGEBOB SQUAREPANTS TO CRITICIZE THE PRACTICE OF YELLOW JOURNALISM - Adyatma, Adham; Eliyanah, Evi; Chotib, Mochamad Nasrul (Universitas Negeri Malang, 2023)
Cartoons as a medium of social criticism have been increasingly popular for the last decades. Famous cartoons targeting adult audiences like South Park and The Simpsons heavily tackle the politics and events in the USA. Children’s cartoons can be equally critical and political. However, scant scholarship still explores the political dimension of children's cartoons. This study aims at filling the scholarly lacuna by looking at how SpongeBob SquarePants, a cartoon dedicated to children, conveys its political message, specifically examining the Krabby Kronicle episode (2008); this article demonstrates that the episode heavily criticizes the practice of yellow journalism through the use of allegory. The allegory is utilized in the narrative to deliver the political message as they try to compare the practice of yellow journalism in the Krabby Kronicle episode and the actual practice of yellow journalism. The allegory is supported by the cinematic (mise-en-scene) aspect of the episode to make the narrative not only entertaining but also make the message believable.